Protein Tyrosine Phosphatases: Regulators of CD4 T Cells in Inflammatory Bowel Disease - Pike, Kelly A.; Tremblay, Michel L. (Frontiers in Immunology, 2018)
Protein tyrosine phosphatases (PTPs) play a critical role in co-ordinating the signaling networks that maintain lymphocyte homeostasis and direct lymphocyte activation. By dephosphorylating tyrosine residues, PTPs have been shown to modulate enzyme activity and both mediate and disrupt protein-protein interactions. Through these molecular mechanisms, PTPs ultimately impact lymphocyte responses to environmental cues such as inflammatory cytokines and chemokines, as well as antigenic stimulation. Mouse models of acute and chronic intestinal inflammation have been shown to be exacerbated in the absence of PTPs such as PTPN2 and PTPN22. This increase in disease severity is due in part to hyper-activation of lymphocytes in the absence of PTP activity. In accordance, human PTPs have been linked to intestinal inflammation. Genome wide association studies (GWAS) identified several PTPs within risk loci for inflammatory bowel disease (IBD). Therapeutically targeting PTP substrates and their associated signaling pathways, such as those implicated in CD4+ T cell responses, has demonstrated clinical efficacy. The current review focuses on the role of PTPs in controlling CD4+ T cell activity in the intestinal mucosa and how disruption of PTP activity in CD4+ T cells can contribute to intestinal inflammation.